11(n-2)+36=3n

Simple and best practice solution for 11(n-2)+36=3n equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11(n-2)+36=3n equation:



11(n-2)+36=3n
We move all terms to the left:
11(n-2)+36-(3n)=0
We add all the numbers together, and all the variables
-3n+11(n-2)+36=0
We multiply parentheses
-3n+11n-22+36=0
We add all the numbers together, and all the variables
8n+14=0
We move all terms containing n to the left, all other terms to the right
8n=-14
n=-14/8
n=-1+3/4

See similar equations:

| 3x/5-1/5=3x/2+5/2 | | 42÷j=62 | | 5n-3=7(n+3)-2n | | 9x–7=–7 | | 9x+7=83 | | -6a+10=2a+10-8a | | (10x-5)+61=180 | | (-2+-10x)=72 | | -2w+14=28 | | 5n-3=7(n+3)-2 | | (10x-5)=180 | | (-10+12x)=86 | | 3(5n+2)=5n+4(2n+4) | | (10x-5)=61 | | 5.5=0.25r | | 5+8(3+x)=13^4x | | 1.5(-7x-1+7=-5 | | 3m-4/4-1/5=m/4+3/10 | | 14(2x+3)=16(5x+21) | | 0.5=0,25r | | 5+8(3+x)=13x4x | | v+7+7=9 | | 5x+12=4x+17 | | (-5x+2)=42 | | 5=x+202=3x-20 | | 20a+–12a=8 | | -4+x=-37 | | 35x-13=53 | | –4+–2y=–10 | | g/50-5/10=2/10 | | r/6+7=-11 | | (16+14x)=128 |

Equations solver categories